Dryland fungi are spatially heterogeneous and resistant to global change drivers - Andrea Lopez; Mark Anthony; Jovani Catalan‐Dibene; Scott Ferrenberg; Samuel E. Jordan; Brooke Osborne; Sasha Reed; Adriana L. Romero‐Olivares (Ecosphere)
Abstract Fungi are considered particularly important in regulating the structure and function of dryland ecosystems, yet the response of dryland fungal communities to global change remains notably understudied. Without a clear understanding of how fungi respond to global change drivers, mitigation plans—required for biodiversity and ecosystem service conservation and restoration—are impossible to develop. In this study, we asked the following: (1) How does the fungal community respond to the individual and interactive effects of physical disturbance and drought in a heterogeneous dryland landscape comprised of drought‐adapted shrubs separated by adjacent open areas of soil? (2) What are the larger scale impacts of this response? We assessed fungal communities (using fungal‐specific DNA metabarcoding analyses) of surface soil samples in an in situ global change experiment that included disturbance and drought in a full factorial design in the northern extent of the Chihuahuan Desert. We found that the fungal community was spatially heterogenous and remarkably resistant to disturbance and drought. We also show that dryland soils harbor high shares of facultative pathogenic and obligately pathogenic fungal taxa, with several concerning taxa reaching high relative abundances under drought. Our results suggest that the fungal community is highly influenced by microclimatic conditions associated with the presence or absence of vegetation. Moreover, our results imply that the fungal community in our experiment was already adapted to the magnitude of stress imposed by two years of experimental disturbance and drought treatments. Overall, our study shows that the fungal community is spatially heterogeneous and resistant to global change drivers and houses many fungal species known for being stress tolerant and pathogenic.